Study on Improving the Fatigue of Newly Designed Mechanical System Such as Hinge Kit System - Seongwoo Woo; Dennis L. O’Neal; Yimer Mohammed Hassen (Technological Innovation in Engineering Research Vol. 1, 2022)
The purpose of this paper is to develop parametric accelerated life testing (ALT) as a systematic reliability method for producing reliability quantitative (RQ) specifications – mission cycle – for recognizing missing design defects in mechanical products. The use of parametric ALT improves the prediction of fatigue failure in mechanical systems subjected to repeated impact loading. It includes: (1) a parametric ALT plan based on the system’s BX lifetime, (2) a fatigue failure and design, (3) tailored ALTs with design options, and (4) a determination of whether the system’s most recent design(s) meets the BX lifetime goal. A generalized life-stress model is proposed, as well as a sample size equation. The concept was demonstrated using a residential refrigerator hinge kit system (HKS), which was a newly designed mechanical device. The HKS was subjected to multiple impact loadings, which resulted in field failure. To figure out how much expedited testing is needed, A force and momentum balance was used to analyze a simple impact loading of the HKS when shutting the refrigerator door. Because the HKS housing failed during the initial ALT, the hinge kit housing was redesigned by attaching inner supporting ribs to the HKS to offer enough mechanical strength against its loading. The torsional shaft in HKS composed of austenitic ductile iron (18 wt% Ni) failed at the second ALT. The 2nd ALTs’ fractured torsional shaft was caused by insufficient rounding that collapsed due to repeated stress. The torsional shaft was altered to give it more rounding from R0.5mm to R2.0mm as part of an action plan to ensure appropriate material strength for the recurring impact loads. There were no issues at third ALT after these changes.